Employing Artificial Intelligence in the Foreign Political Decision-Making - Sami, PhD. Ali Ghassan (The college of law and political science journal, 2023)
This study has contributed to determining what AI is, its genesis, its most important types and dimensions and outline the concept and phases of external political decision-making, as well as addressing the role and impact of intelligence techniques on the effectiveness of external political decision-making As AI applications have been shown to help build simulated models for foreign policy decision-making, AI capabilities are able to process an enormous amount of data stored on international relations and public opinion, as well as positions and alliances of States to prepare a package of options and alternatives in support of external political decision-making Those alternatives will be able to deal with emerging crises and international emerging situations, It is well known that the decision-making process is expanding in all economic areas. Social, political, military, etc., in which AI technologies are heavily influenced to make it more effective in times of peace or war.